How Stress Influences The Physiological Functions Of The Human Body: A Bibliometric Mapping 2019-2024 - Saminan, Saminan; Linda Julisafrida; Saminan, Nurul Fajri; Muhammad Khairul (Sean Institute, 2024)
Stress is an important component of modern life and has been widely recognized as a factor that negatively impacts health. The aim of this research is to map the influence of stress on the physiological functions of the human body over the last five years (2019–2024) using data from the Scopus database. Bibliometric analysis was conducted with VOSviewer visualization to depict publication patterns, citations, keywords, and relation-ships between concepts. The results indicate that the United States was the country with the highest number of publications in 2019, with 110 documents. Overall, the keywords